Study guides

☆☆

Q: X2 plus 3x-7 equals 5x plus 8?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x2 + 5x + 3 = 9 x2 + 5x - 6 = 0 (x + 6)(x - 1) = 0 x = -6 or x = 1

We can't calculate what it equals until we know the value of ' x '.

x2 + 5x - 120 can not be factored.

x2+4x-9 = 5x+3 x2+4x-5x-9-3 = 0 x2-x-12 = 0 (x+3)(x-4) = 0 x = -3 or x = 4

x2 + 5x + 6 = (x + 2)(x + 3)

Related questions

x2 + 5x + 3 = 9 x2 + 5x - 6 = 0 (x + 6)(x - 1) = 0 x = -6 or x = 1

x2-5x+4 = (x-1)(x-4) when factord

We can't calculate what it equals until we know the value of ' x '.

-x2 + 5x - 4 = 0. Then, x2 - 5x + 4 = (x - 4)(x - 1) = 0; whence, x = 1 or 4. Checking, -1 + 5 - 4 = 0; and -16 + 20 - 4 = 0.

x2 + 4x - 9 = 5x + 3 ∴ x2 - x - 12 = 0 ∴ (x + 3)(x - 4) = 0 ∴ x ∈ {-3, 4}

x2 + 5x - 120 can not be factored.

x2+4x-9 = 5x+3 x2+4x-5x-9-3 = 0 x2-x-12 = 0 (x+3)(x-4) = 0 x = -3 or x = 4

the question is to solve (x^2-5x+5)^(x^2-36)=1

x2 + 5x + 6 = (x + 2)(x + 3)

x2 - 5x = 0x (x - 5) = 0x = 0andx = 5

You don't factor an equation. You factor an expression.So we'll forget about the "equals 0" for a second, while we factor "x2 plus 5x plus 6".x2 + 5x + 6 = (x + 3) (x + 2).Now, if you want this expression to be equal to zero, that can only happen when 'x' is -2 or -3.

People also asked